Synthesis of perovskite-alumina gel for membrane preparation by sol-gel technique - Idrus, Nor Faeqah; Ahmad, Abdul Latif; Othman, Mohd. Roslee (Penerbit Universiti Sains Malaysia, 2004)
The potential application of inorganic alumina membranes in separation, filtration and catalytic reactions has preferential research on synthesis, characterization and property improvement of inorganic alumina membranes because of their unique features.